A New Challenge in Treatment of Sarcopenic Obesity in Older Adults: A Systematic Review - Parmelia, Manik; Sastrawan, I Gede Agus; Kenwa, Komang (Journal of Ageing And Family, 2023)
Introduction: Sarcopenic obesity (SO) defined as a phenotype of coexistence of sarcopenia, is an age-related loss of muscle mass and strength or physical performance, and obesity. It is crucial to determine the best management strategy for sarcopenic obese patients in order to improve life expectancy. The goal of this review is to provide an overview of sarcopenic obesity treatment for older persons. Methods: PubMed searches were conducted for ‘sarcopenic obesity treatment’ and ‘sarcopenic obesity elderly treatment’ from a database through the past 10 years. All articles available in English identified by these searches were then reviewed in detail Result: At present, the optimal treatment of sarcopenic has not been established. Nutritional interventions, such as a hypocaloric diet, and exercise training or physical therapy are the mainstay of SO prevention and treatment to achieve changes in body composition (muscle gain and fat reduction) and improve the functional status and quality of life of elderly patients. Conclusion: To further our understanding of SO, it is essential that clinicians and researchers establish a universal consensus for the definition and diagnosis of SO and focus on SO treatment and promote healthy aging. Keywords: sarcopenic obesity, elderly, treatment